(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
Airoldi (1930, 1932) described twenty-three fossil Corallinales (Rhodophyta) from the Oligocene of the Tertiary Piedmont Basin (NW Italy), including thirteen new species. In this paper Mesophyllum fructiferum Airoldi 1932 and Mesophyllum obsitum Airoldi 1932 are re-documented and re-described. The presence of cell fusions, multiporate conceptacles and a ventral core of cell filaments passing from coaxial to non-coaxial confirm that both species belong to the genus Mesophyllum. SHORT NOTES